Protective effect of breastfeeding on Kawasaki disease: A systemic review and meta-analysis - Wan-Jung Yang; Wen-Hsien Lu; Yu-Yang Hsiao; Tien-Wei Hsu; Yee-Hsuan Chiou (Pediatrics and Neonatology)
Background: Previous research has indicated a negative correlation between exclusive breastfeeding and the incidence of Kawasaki disease (KD). However, the validation of this discovery through meta-analytical studies has been lacking. Furthermore, uncertainties persist regarding whether breastfeeding reduces the risk of coronary artery lesions (CAL) or resistance to intravenous immunoglobulin (IVIG). Methods: A systematic exploration of the MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, EMBASE, and ClinicalTrials.gov databases was conducted to identify longitudinal or randomized controlled trials investigating the efficacy of breastfeeding in preventing KD. The primary focus was on the incidence of KD, with secondary emphasis placed on the incidence of CAL and IVIG resistance. Data were pooled using a frequentist-restricted maximum-likelihood random-effects model. Results: Of the 179 potentially eligible studies identified, five (n = 1,982,634) were included. The analysis revealed a significantly lower risk of KD (expressed as odds ratio, with 95% confidence intervals and p-values) in comparisons between exclusive breastfeeding and formula feeding (0.62, 0.43−0.91, p = 0.014), exclusive breastfeeding/partial breastfeeding and formula feeding (0.66, 0.46− 0.96, p = 0.03), and exclusive breastfeeding and partial breastfeeding/formula feeding (0.81, 0.74− 0.90, p < 0.01). However, no significant difference was observed in the risk of developing KD when comparing partial breastfeeding to formula feeding exclusively. Regarding secondary outcomes, no statistically significant difference was found in the risk of CAL or IVIG resistance across any comparison formats. Conclusions: Our study suggests that breastfeeding correlated with a reduced risk of KD but not with a reduced risk of CAL or IVIG resistance. These findings advocate for the implementation of breastfeeding policies in clinical practice.